Visions : nineteen short stories by outstanding writers for young adults - Gallo, Donald R. (New York : Delacorte Press, 1987)
Nineteen short stories, dealing with teenage concerns, written especially for this collection by well-known authors of young adult novels such as Joan Aiken, M.E. Kerr, Richard Peck, and Colby Rodowsky. Also includes biographical sketches for each author.
Notable/Best Books (A.L.A.).
School Library Journal starred.
Wilson's Junior High School.
6.7
7-10.
Young Adult
Keywords: Short stories; Short stories